Lung ultrasound: diagnostic and therapeutic issues - Cattarossi, L. (Acta Biomedica Atenei Parmensis, 2014)
Background: Lung ultrasound (LUS) is becoming more and more utilised in the clinical field inadults, children and neonates in course of respiratory diseases. It can be done at bed side and repeated as muchis needed without risks (namely irradiation). Methods: The technique of LUS execution and the normal andpathologic patterns of LUS in neonates are described. Results: The LUS findings in the different respiratoryneonatal diseases are peculiar and consistently repeatable. Conclusion: The use of LUS in neonates may indicatein real time the diagnosis of the respiratory disease. Should be considered as an extension of the clinicalexam and must be done by the clinician in charge of the patient.